Social Environment Has a Primary Influence on the Microbial and Odor Profiles of a Chemically Signaling Songbird - Whittaker, Danielle J.; Gerlach, Nicole M.; Slowinski, Samuel P.; Corcoran, Kyle P.; Winters, Andrew D.; Soini, Helena A.; Novotny, Milos V.; Ketterson, Ellen D.; Theis, Kevin R. (Frontiers in Ecology and Evolution, 2016)
Chemical signaling is an underappreciated means of communication among birds, as may be the potential contributions of symbiotic microbes to animal chemical communication in general. The dark-eyed junco (Junco hyemalis) produces and detects volatile compounds that may be important in reproductive behavior. These compounds are found in preen oil secreted by the uropygial gland, and this gland supports diverse bacterial communities including genera known to produce some of these volatile compounds. We investigated the relative contributions of shared environments and genetic relatedness in shaping juncos’ symbiotic bacterial communities, and investigated whether these bacterial communities underlie juncos’ chemical signaling behavior. We sampled parents and nestlings at 9 junco nests during one breeding season at Mountain Lake Biological Station in Virginia, USA. From each individual, we collected swabs of the uropygial gland and the cloaca, preen oil, and a small blood sample for paternity testing. We characterized junco bacterial communities through 16S rRNA gene surveys and preen oil volatile compounds via gas chromatography-mass spectrometry. Nest membership and age class had the strongest influence on the structure of bacterial and volatile profiles. We compared father-offspring similarity based on paternity, and nestling similarity in nests containing full siblings and half siblings, and found that relatedness did not noticeably affect bacterial or volatile profiles. While we cannot rule out an influence of genetic relatedness on these profiles, it is clear that shared environments are more influential in shaping bacterial and volatile profiles among juncos. We did not find significant covariation between individual bacterial and volatile profiles. Possible explanations for this result include: 1) bacteria do not underlie volatile production; 2) ample redundancy in volatile production among bacterial types obscures covariation; or 3) the relationship is confounded by the fact that, unlike glands exclusively dedicated to chemical communication, uropygial glands have multiple functions, and symbiotic bacteria are hypothesized to contribute to each of these. Therefore, different bacteria may contribute to different phenotypes of the avian holobiont. Future work will include cultivation, metabolomic, genomic, and behavioral assay approaches to tease these scenarios apart.